Research Ethics Board of Health: a seven year review of the only ethics review board in Bhutan - Mongal S. Gurung; Tashi Dema; Dorji Pelzom; Tashi Tobgay; Pakila Drukpa (Bhutan Health Journal, 2016)
Introduction: Research Ethics Board of Health (REBH), established in 2009, is the only ethics review board in Bhutan. The REBH was certified by the Strategic Initiative for Developing Capacity in Ethical Review (SIDCER), Forum for Ethical Review Committees in the Asian and Western Pacific Regions (FERCAP) in 2010 and recertified in 2013, and it received the Federal Wide Assurance (FWA) from the Office for Human Research Protections (OHRP), USA, in 2010 and in 2013. All researchers conducting health related research in Bhutan have to seek prior ethical clearance from REBH under the requirements of the National Health Policy 2011. Objective: The article aims to describe the performance of REBH, its standard and review procedure.